Effectiveness and Implementation of Multicomponent Neuromuscular Training Programs for Lower Extremity Injury Prevention in Adolescent Team Sport Athletes: A Systematic Review of Systematic Reviews and Meta‑analyses - Walczak, Paulina; Niewęgłowska, Małgorzata; Bender, Aleksandra; Widomska, Katarzyna; Bernad, Mateusz; Krazińska, Oliwia; Gałach, Magdalena; Łukaszewicz, Jakub; Dąbrowski, Kacper; Szymulewicz, Bartłomiej; et al. (Quality in Sport, 2026)
Background: Adolescent athletes participating in team sports are at high risk of lower extremity injuries, particularly knee and ankle injuries, including anterior cruciate ligament (ACL) ruptures. Multicomponent neuromuscular training (NMT) programs combining strength, plyometric, balance, agility, and movement-control exercises are widely used for injury prevention. Objective: To synthesize evidence from systematic reviews and meta-analyses on the effectiveness of NMT programs and factors influencing their implementation in adolescent team-sport athletes. Methods: An umbrella review of systematic reviews and meta-analyses was conducted. Reviews evaluating exercise-based injury prevention programs in sport were included. Data on injury outcomes, effect estimates, and implementation factors were extracted and synthesized narratively. Results: Multicomponent NMT programs consistently reduced injury risk. In adolescent athletes, total injuries were reduced by approximately 35% (IRR 0.65) and lower extremity injuries by 33% (IRR 0.67). Greater effects were observed for ankle injuries and in female athletes. Short programs (<20 minutes), integrated into warm-ups and performed 2–3 times weekly, were most effective. Higher adherence was associated with greater injury reduction. Conclusions: Multicomponent NMT programs successfully reduce lower-extremity injuries among adolescent team-sport athletes, particularly among females. Brief, well-structured programs integrated into routine training and supported by appropriate implementation strategies remain crucial to maximize their effectiveness.